2011
DOI: 10.1002/chem.201101590
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Access to α‐Alkoxy and α‐Amino Acid Derivatives through Safe Continuous‐Flow Generation of Diazoesters

Abstract: Despite the wide synthetic potential of diazo compounds (XÀH insertion, ylide formation, cyclopropanation, cycloaddition etc.), [1] concerns over the hazards associated with their preparation, isolation, and use have hindered their full exploitation in both academic and industrial laboratories. A few diazo compounds are commercially available (e.g. ethyl and butyl diazoacetate, TMS-diazomethane and diazodimedone), [2] but safe and convenient access to a wider range of useful functionalized diazo species is st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 26 publications
(30 reference statements)
1
47
0
1
Order By: Relevance
“…Bartrum et al [18] published a flow synthesis of numerous diazo esters starting from the corresponding arylsulfonylhydrazones, where the diazo moiety was installed through elimination of the sulfone substituent. Additionally, Ley et al [19] recently prepared a range of α-hydroxy acids in flow starting from the corresponding amino acids, involving diazotization of the amine to the diazonium salt in a biphasic system.…”
Section: Introductionmentioning
confidence: 99%
“…Bartrum et al [18] published a flow synthesis of numerous diazo esters starting from the corresponding arylsulfonylhydrazones, where the diazo moiety was installed through elimination of the sulfone substituent. Additionally, Ley et al [19] recently prepared a range of α-hydroxy acids in flow starting from the corresponding amino acids, involving diazotization of the amine to the diazonium salt in a biphasic system.…”
Section: Introductionmentioning
confidence: 99%
“…In order to address this problem, we, and others, have shown that diazo compounds can be generated safely under continuous flow chemistry conditions,5 thus limiting the exposure and hence hazards previously associated with these reactive compounds. In our previous work we have shown that in‐flow base treatment of sulfonyl hydrazones gives ready access to diazo compounds, and we have shown that these can be used directly in a variety of synthetically useful transformations 6,7. Although this represented a significant improvement of existing methods for in‐flow generation of diazo compounds such as the use nitrosamine precursors,810 or sulfonyl azides,11 the production of stoichiometric quantities of 4‐toluenesulfinate as waste results in overall poor atom economy, and further work was required to address this shortcoming.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, longer‐chain aliphatic or branched aliphatic diazo esters were obtained only in moderate yield. In a subsequent batch transformation, Hayes, Moody and co‐workers described the rhodium(II) catalyzed O−H and N−H insertion reactions of these diazo esters (Scheme ) . In a further report, Moody, Hayes and co‐workers extended this protocol to rhodium, and copper catalyzed insertion reactions with thiols, sulfinates and phosphonates …”
Section: Bamford–stevens Reactionsmentioning
confidence: 99%
“…In as ubsequent batch transformation, Hayes, Moody and co-workers describedt he rhodium(II) catalyzed OÀHa nd NÀHi nsertion reactions of these diazo esters (Scheme 10). [37] In af urtherr eport, Moody,H ayes and co-work-Scheme8.Iterativecoupling of diazo compounds with boronic acids.…”
Section: Bamford-stevens Reactionsmentioning
confidence: 99%